The Political Theology of Commemoration: Global South Perspectives on 500 Years of Reformation. Issue 2 (July 2017) - Mtata, Kenneth
Abstract: The 2017 commemoration of the Reformation is an opportunity to reflect on the dynamic of the Reformation as a phenomenon of change, change that seems to be needed in many aspects of our globalized world. This article looks at elements of the Reformation for their potential to energize social transformation today through a particular combination of the "old" and the "new" catalyzed by the Holy Spirit, focusing on law (addressing power asymmetries), the gospel (embracing emerging life), and the scriptures.